Cover Picture: A Macromolecular Drug for Cancer Therapy via Extracellular Calcification (Angew. Chem. Int. Ed. 12/2021). Issue 12 (15th February 2021) - Tang, Ning; Li, Hanhui; Zhang, Lihong; Zhang, Xueyun; Chen, Yanni; Shou, Hao; Feng, Shuaishuai; Chen, Xinhua; Luo, Yan; Tang, Ruikang; Wang, Ben
Abstract : A macromolecular drug, polysialic acid conjugated with folate (folate‐polySia), was developed by Ruikang Tang, Ben Wang et al. as an extracellular chemotherapy drug involving biomineralization for malignant tumor diseases in their Research Article on page 6509 . The new type of drug combines with folate receptor and selectively induces biogenic mineral formation on tumor cells via absorbing calcium from the blood, resulting in the pathological calcification of tumors. Administration of folate‐polySia inhibits tumor growth and dramatically improved the survival rates of mice.